KELEKATAN ANAK PADA ORANG TUA DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF DAN HARGA DIRI - Amita Diananda (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
Parental attachment does unequivocally have a pivotal relationship with emotion. Parent, especially a mom, is the first and foremost person who has the emotion bond with her child. This bond affects the most of the development of a child. The absent of fulfilment of emotion needs in caregiving of a child, such as a feeling of safety, love and/or compassion, attention, and appreciation, will take an innocent child to a stage of susceptibility that will drive him to be a “vulnerable child” that is a child with fragile personality, frail, fearful, lack of contentment and happiness, et cetera. Parental attachment in the period of growth and development can help challenging tasks so as to trigger cognitive development to the fullest and the growing of sense of self-esteem of a child. This research is using a qualitative approach and analysis, while the type of research is library research.